The Effect of Scoring Skill and Opponent Errors on the Team Wins of the Final Four Proliga Volleyball Team Participants 2019 - Apriyanto, Tirto; Asmaw, Moch.; Hanif, Sofyan (KnE Social Sciences, 2020)
This study aims to determine and prove the direct effect of scoring skills (service, spike, block) and opponent error on the team wins of the four Proliga volleyball teams participating in the 2019 finals. The research method used is a survey method with analysis techniques using the path analysis approach. A total sampling technique was used and data collection was carried out based on the indicators contained in the Volleyball Information System (VIS). The results of the study concluded that: (1) service has a direct but not significant effect on opponent error by 2.34%; (2) spike has a direct effect on opponent error by 5.76%; (3) the block has a direct but not significant effect on opponent error by 0.27%; (4) opponent error directly affects the team wins by 16.4%; (5) service has a direct effect by 8.61%; (6) spike has a direct effect by 33.8%; (7) block has a direct effect on the team wins of by 21.68%. Keywords: scoring skills, opponent error, team wins.